2011
DOI: 10.1159/000329616
|View full text |Cite
|
Sign up to set email alerts
|

Cx40 Is Required for, and Cx37 Limits, Postischemic Hindlimb Perfusion, Survival and Recovery

Abstract: Background/Aims: Ischemia induced by large-vessel obstruction or vascular injury induces a complex cascade of vasodilatory, remodeling and inflammatory pathways; coordination of these processes by vascular endothelium is likely to involve endothelial gap junctions. Vascular endothelium predominantly expresses two connexin (Cx) isoforms: Cx37 and Cx40. The relevance of these Cxs to postischemic limb recovery remains unclear. Methods: In this study, we use a well-established, severe femoral-saphenous artery-vein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 57 publications
3
37
0
Order By: Relevance
“…We showed previously that tissue survival and recovery were compromised in Cx40-deficient mice subjected to the severe form of hindlimb ischemia that eliminates flow to the major collateral vessels supplying the distal hindlimb (15). Generally, survival and recovery of ischemic tissue is determined, in large part, by the magnitude and area of blood flow Ϫ/Ϫ no losartan, n ϭ 13, 3-day losartan, n ϭ 7, 8-wk losartan, n ϭ 9; mild surgery: no losartan, n ϭ 10, 8-wk losartan, n ϭ 11; use data, severe surgery: no losartan, n ϭ 11, 3-day losartan, n ϭ 7, 8-wk losartan, n ϭ 9; mild surgery: no losartan, n ϭ 10, 8-wk losartan, n ϭ 11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We showed previously that tissue survival and recovery were compromised in Cx40-deficient mice subjected to the severe form of hindlimb ischemia that eliminates flow to the major collateral vessels supplying the distal hindlimb (15). Generally, survival and recovery of ischemic tissue is determined, in large part, by the magnitude and area of blood flow Ϫ/Ϫ no losartan, n ϭ 13, 3-day losartan, n ϭ 7, 8-wk losartan, n ϭ 9; mild surgery: no losartan, n ϭ 10, 8-wk losartan, n ϭ 11; use data, severe surgery: no losartan, n ϭ 11, 3-day losartan, n ϭ 7, 8-wk losartan, n ϭ 9; mild surgery: no losartan, n ϭ 10, 8-wk losartan, n ϭ 11].…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral hindlimb ischemia was induced by one of two surgical strategies: femoral and saphenous artery-vein pair resection, here termed severe surgery, and femoral artery ligation, here termed mild surgery, as previously described (14,15). For the severe surgery, ligatures were placed around the femoral artery-vein pair upstream of the epigastric and gracilis artery branch-points and around the saphenous artery-vein pair midway between the knee and ankle, and the intervening lengths of vessel were resected.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in endothelial cells, Cx37 and Cx40 are collectively essential for vascular development [29]. Recently, it was shown that Cx40 and Cx37 have opposite effects on postischemic limb perfusion, recovery, and tissue survival in the same mouse model [30]. Another example is the expression of Cx31 and Cx43 during preimplantation development.…”
Section: F137l/f137lmentioning
confidence: 99%